Aspergillus fumigatus Endophthalmitis with Necrotizing Scleritis following Pars Plana Vitrectomy. (9th June 2016) - Gruener, Anna M.; Allen, Felicity; Stanford, Miles R.; Graham, Elizabeth M.
Abstract : We present a case of Aspergillus fumigatus endophthalmitis complicated by necrotizing scleritis in a 68-year-old man with diet-controlled diabetes, after retinal detachment repair. He was initially treated with systemic steroids for surgically induced necrotizing scleritis following routine pars plana vitrectomy. An additional diagnosis of endophthalmitis was made when the patient developed a hypopyon. Repeat vitreous culture isolated Aspergillus fumigatus . Symptoms improved following antifungal treatment leaving the patient with scleromalacia and an advanced postoperative cataract. Fungal scleritis and endophthalmitis are rare complications of intraocular surgery with sight-threatening consequences, and, as this case demonstrates, may even occur concomitantly. The overlapping features of both conditions can make differentiating one from the other difficult. A fungal aetiology should be considered in cases of postoperative scleritis and endophthalmitis that are protracted and refractory to standard therapy. Even in cases of early diagnosis and treatment, visual outcomes in Aspergillus endophthalmitis and scleritis are variable and often disappointing, not infrequently necessitating enucleation of a painful blind eye.